The economic invalidity of fiat money from an islamic outlook - Adam Abdullah (Fakulti Pengurusan dan Ekonomi, 2012)
This research focuses on the role of money, the development of money and banking and monetary reform. The research demonstrates that the migration of the medium of exchange from gold and silver into a legal tender involving flat paper notes and bank deposits backed by debt, reflects a reduction of intrinsic value, even though the token value of fiat money is still considered as equivalent in value to the intrinsic value of historical coinage: money has developed from physical gold and silver into virtual payments.